Diagnostic Efficacy of Rectal Suction Biopsy with Regard to Weight in Children Investigated for Hirschsprung's Disease - Emma Fransson; Christina Granéli; Kristine Hagelsteen; Louise Tofft; Mette Hambraeus; Rodrigo Urdar Munoz Mitev; David Gisselsson; Pernilla Stenström (MDPI AG, 2022)
Background/aim: Diagnostic efficacy, defined as the percentage of rectal suction biopsy (RSB) specimens sufficient enough to determine the absence of ganglia cells in Hirschsprung's disease (HD) diagnosis, has been reported to be low, requiring repeated biopsies. The aim was to explore whether RSB diagnostic efficacy was influenced by the child's weight and to ascertain whether RSB efficacy differed between aganglionic and ganglionic tissue. Materials and Methods: Efficacy analyses were conducted in a national HD-center's register on children 0-15 kg, examined between 2011-2019. First-time RSB diagnostic efficacy was correlated to the children's weight and final HD diagnosis. Results: Among the 84 children who had first-time RSB, the overall diagnostic efficacy was 85% (71/84). The efficacy was higher among children weighing less than the identified cut-off of 9.0 kg (89% in 0-9.0 kg versus 62% in 9.01-15.0 kg, p = 0.026). Among children diagnosed with HD, 96% (26/27) weighed 0-9.0 kg. In this weight group, the diagnostic efficacy was lower in aganglionosis compared to ganglionosis (77%; 20/26 versus 96%; 43/45), p = 0.045). Conclusions: The RSB diagnostic efficacy was significantly higher in children weighing less than 9.0 kg and was less in aganglionic compared to ganglionic tissue. Therefore, weight can be useful to predict RSB diagnostic efficacy.